2012
DOI: 10.1371/journal.pone.0030857
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Sexual Maturation and Mating in the Mediterranean Fruit Fly, Ceratitis capitata

Abstract: Sexual maturation and mating in insects are generally accompanied by major physiological and behavioural changes. Many of these changes are related to the need to locate a mate and subsequently, in the case of females, to switch from mate searching to oviposition behaviour. The prodigious reproductive capacity of the Mediterranean fruit fly, Ceratitis capitata, is one of the factors that has led to its success as an invasive pest species. To identify the molecular changes related to maturation and mating statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 102 publications
(119 reference statements)
5
74
3
Order By: Relevance
“…These transcriptomic approaches offer a means of directly exploring which genes are associated with complex phenotypes such as behaviour, and experiments can reveal changes in gene regulation associated with changes in those phenotypes. For instance, recent work has revealed some of the genes and genetic networks associated with changes in female behaviour after mating in species of Drosophila [24][30], the Mediterranean fruit fly Ceratitis capitata [31], the honey bee Apis mellifera [32], [33], and the parasitoid wasp Nasonia vitripennis (R. Watt, U. Trivedi, T.J. Park, M. Blaxter and D.M. Shuker, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…These transcriptomic approaches offer a means of directly exploring which genes are associated with complex phenotypes such as behaviour, and experiments can reveal changes in gene regulation associated with changes in those phenotypes. For instance, recent work has revealed some of the genes and genetic networks associated with changes in female behaviour after mating in species of Drosophila [24][30], the Mediterranean fruit fly Ceratitis capitata [31], the honey bee Apis mellifera [32], [33], and the parasitoid wasp Nasonia vitripennis (R. Watt, U. Trivedi, T.J. Park, M. Blaxter and D.M. Shuker, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…2016b). A handful of genes are known to change expression following mating in male D. melanogaster (Ellis and Carney 2010) and Ceratitis capitata (Gomulski et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In our experimental design for the EST libraries construction, the maturation process is more prone to be unveiled, as mating was allowed. Despite this limitation our results could be more realistic as some biological and cellular processes are also modulated by mating status, as demonstrated by Moshitzky et al (2003) or by Gomulski et al (2012). These authors have demonstrated that mating can modulate the biosynthesis of juvenile hormones in medfly females (the male specific serum proteins and peptides are the responsible of down-regulation of the juvenile hormones in the mated females when compared to virgin females of the same age).…”
Section: Discussionmentioning
confidence: 89%
“…Each consensus sequence was compared to GenBank by blast using tblastx as implemented in NCBI web page to assign gene function (Altschul et al, 1997). Sequences were also compared to those EST (expressed sequence tags) available of C. capitata in dbEST (GenBank: FG068301−FG089553; Gomulski et al, 2012). Gene ontology (GO) was established by assignment of each identified gene function into GO browser.…”
Section: Unigene Set Establishmentmentioning
confidence: 99%